Technical guidelines for the safe movement of cacao germplasm. Revised from the FAO/IPGRI Technical Guidelines No. 20 (Third Update, October 2017) - End, M.J.; Daymond, Andrew J.; Hadley, P.; Global Cacao Genetic Resources Network; Bioversity International (2017)
These guidelines describe technical procedures that minimize the risk of pest introductions with movement of cacao germplasm for research, crop improvement, plant breeding, exploration or conservation.